Bone Mineral Density Declines Twice as Quickly Among HIV-Infected Women Compared With Men. (1st March 2018) - Erlandson, Kristine M.; Lake, Jordan E.; Sim, Myung; Falutz, Julian; Prado, Carla M.; Domingues da Silva, Ana Rita; Brown, Todd T.; Guaraldi, Giovanni
Abstract : Background: Initial declines in bone mineral density (BMD) after antiretroviral therapy initiation in HIV are well described, but data on long-term changes and risk factors for decline, particularly among women, are limited. Methods: HIV-infected men and women in the Modena Metabolic Clinic underwent dual-energy X-ray absorptiometry (DXA) scans every 6–12 months for up to 10 years (median 4.6 years). Mixed effect regression models in combined and sex-stratified models determined annual rates of decline and clinical factors associated with BMD. Models included demographics, HIV-specific factors, and bone-specific factors; a final model added a sex × time interaction term. Results: A total of 839 women and 1759 men contributed ≥2 DXA scans. The majority (82%) were 50 years and younger; 76% had HIV-1 RNA <50 copies per milliliter at baseline; 15% of women were postmenopausal and 7% of men had hypogonadism; and 30% and 27%, respectively, had hepatitis C virus (HCV) coinfection. The adjusted slopes in BMD among women and men were significantly different at both the femoral neck (women −0.00897 versus men −0.00422 g/cm 2 per year; P < 0.001) and L-spine (women −0.0127 versus men −0.00763 g/cm 2 per year; P < 0.001). Modifiable risks associated with BMD decline included antiretroviral therapy exposure (greater decline with tenofovir disoproxil fumarate and less decline with integrase strand transfer inhibitor therapy), HCV, physical activity, and vitamin D insufficiency. Conclusions: Among HIV-infected individuals, bone density at the femoral neck, a significant predictor of fracture risk, declined twice as quickly among women compared with men. Female sex was independently associated with both lower femoral neck and lumbar BMD over time in adjusted models.